Muslim consumer rights based on Islamic advertising principles - Nur Hikmah Yahya; Rosmawati Mohamad Rasit (Penerbit Universiti Kebangsaan Malaysia, 2019)
The advertising industry is one of the biggest contributors to the nation’s Gross Domestic Product (GDP) and helps the local agencies in developing the nation’s economy. However, the Islamic advertising has not been clearly discussed in the National Advertising Policy. This creates a scenario where advertisement aired does not comply with the Muslim consumer rights as they are misleading and endangering consumer’s safety as well as overclaiming. There is also the abuse that occurred in relation to use of the halal logo and the use of models in the ads that do not meet the Sharia that can influence the behaviour of consumer, especially Muslim consumer. Therefore, this study was undertaken with the aim to examine Muslim consumer rights based on the Islamic advertising principles. The study used a descriptive qualitative approach by using semi-structured interview data collection method, while for selecting the informants it used purposive sampling. The data analysis was done using constant comparative analysis. The findings showed that there are eight important aspects in preserving Muslim consumer rights based on the Islamic advertising principles. Advertisers and consumers play an important role to this eight important aspect to safeguard the Muslim consumer rights. The findings discussed that the Islamic advertising principles help shape smart and bold Muslim consumers who are vocal enough standing for personal, cultural and religious wellbeing. The implications of this study to make those advertisers and consumers as individuals who are very meticulous about their right and responsibility in creating the market more transparent.